Service Quality Ditinjau dari Kepemimpinan Transformasional Pimpinan Yayasan Terhadap Guru Pesantren - Tria Sari; Winida Marpaung; Diny Atrizka (Psyche 165 Journal, 2020)
This study aims to determine the relationship between transformational leadership and service quality. The hypothesis proposed in this study is that there is a positive relationship between transformational leadership and service quality, assuming the higher the transformational leadership, the higher the service quality and vice versa. The research subjects used in this study were Darul Arafah Islamic Boarding School teachers in Lau Bakeri Deli Serdang, as many as 100 people. Data collection techniques using purposive sampling. The research data were obtained using transformational leadership scale and service quality. Analysis of the data used is to use product moment correlation through SPSS 17 for windows. The results of data analysis showed a correlation coefficient of r = 0.532 and a significance value of 0.000 (p <0.05). Based on the results of this study it can be concluded that the research hypothesis is accepted, namely there is a positive relationship between transformational leadership and service quality.